1973
DOI: 10.1172/jci107248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraluminal Flow on Proximal Tubular Reabsorption

Abstract: A B S T R A C T Micropuncture techniques in the rat were used to reinvestigate the possibility that intraluminal flow rate per se may influence net volume reabsorption by the proximal tubule. An experimental design was devised which lowered intraluminal flow without affecting filtration rate of the nephron under study or without directly affecting other renal hemodynamics. In 11 rats flow of tubular fluid between early and late proximal tubular sites was reduced by partially collecting tubular fluid at the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 27 publications
3
74
2
Order By: Relevance
“…Osmolality and pH were measured on urine samples. Timed collections of tubular fluid were obtained from four or five last proximal tubular loops with oil-filled micropipettes (8-10 j,m OD) as previously described (15). Using a servo-null pressure apparatus (Instrumentation for Physiology and Medicine, San Diego, Calif.), hydrostatic pressures were measured in 5-10 proximal tubules, 3-5 efferent arterioles, and 5-10 peritubular capillaries.…”
Section: Methodsmentioning
confidence: 99%
“…Osmolality and pH were measured on urine samples. Timed collections of tubular fluid were obtained from four or five last proximal tubular loops with oil-filled micropipettes (8-10 j,m OD) as previously described (15). Using a servo-null pressure apparatus (Instrumentation for Physiology and Medicine, San Diego, Calif.), hydrostatic pressures were measured in 5-10 proximal tubules, 3-5 efferent arterioles, and 5-10 peritubular capillaries.…”
Section: Methodsmentioning
confidence: 99%
“…14 littermate 10-d postpartum Munich Wistar rats weighing 200-265 g were prepared for clearance and micropuncture studies as described (13 (10 ,ul) were taken at the beginning and end of the series of efferent arteriolar blood collections. The animals were then infused via the femoral vein with endotoxin for two h as in the preceding set of experiments and the measurements described above were repeated.…”
Section: Snffmentioning
confidence: 99%
“…Recent studies have shown that GFR calculated from distal tubular fluid collections are consistently lower than those calculated from proximal tubular fluid collections in that nephron, when distal tubular sodium concentration are presumably very low due to the proximal oil block (57,58). Others have failed to substantiate these findings (59).…”
Section: Microinjection Studiesmentioning
confidence: 99%